2019
DOI: 10.1186/s12978-019-0749-y
|View full text |Cite
|
Sign up to set email alerts
|

Male partner influence on family planning and contraceptive use: perspectives from community members and healthcare providers in KwaZulu-Natal, South Africa

Abstract: Background South Africa faces numerous reproductive challenges that include high rates of unplanned and adolescent pregnancies. The uptake and utilization of family planning services and modern contraception methods depend on numerous factors. The male partner plays a key role in reproductive health but data on this topic are outdated or have a predominant HIV prevention focus. The purpose of this paper is to explore the influence of male partners on family planning and contraceptive (FP/C) uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
196
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 53 publications
13
196
1
7
Order By: Relevance
“…While some male participants reported to support contraceptive use, others did not. This seemed related to the norm that men with many children gain more respect, but also to misconceptions about contraceptives, in particular that they reduce men's sexual performance [11,27]. Kaneka and Mturi (2017), in their further analysis regarding the abovementioned study, found that husbands' resistance to contraceptive use was related to their desire to exert control over the sexual and reproductive lives of their wives.…”
Section: Discussionmentioning
confidence: 97%
“…While some male participants reported to support contraceptive use, others did not. This seemed related to the norm that men with many children gain more respect, but also to misconceptions about contraceptives, in particular that they reduce men's sexual performance [11,27]. Kaneka and Mturi (2017), in their further analysis regarding the abovementioned study, found that husbands' resistance to contraceptive use was related to their desire to exert control over the sexual and reproductive lives of their wives.…”
Section: Discussionmentioning
confidence: 97%
“…In this manuscript, we speci cally explored community participation practices and activities according community and healthcare provider perspectives. Other exploratory qualitative research activities are published elsewhere [15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…Yolandie Kriel, Cecilia Milford et al [21] explore the perception and attitude towards of male family planning and contraceptive (FP/C) uptake, whether positively or negatively and It use is important in intercepting inadvertent pregnancies and improving FP policy and services delivery programs in South Africa.…”
Section: Issue and Challenges Of Adopting Contraception Methods By Mementioning
confidence: 99%